2021
DOI: 10.3389/fnut.2021.722450
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Cholesterol Intake With Risk of Gastric Cancer: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Many case–control studies have investigated the association between dietary cholesterol and gastric cancer, yielding inconsistent findings. We carried out a systematic review and meta-analysis of observational studies to assess the relationship between dietary cholesterol intake and gastric cancer among adults.Methods: PubMed, Scopus, and Google Scholar were systematically searched to identify articles that evaluated the association of dietary cholesterol with gastric cancer up to May 2021. Pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…The increased cholesterol levels in sera of upper GI cancer patients compared with PanC patients is a further sign of prolonged starvation because it has been shown that starvation triggers cholesterol release from lysosomes 38 . However, it cannot be excluded that the elevated cholesterol levels are a consequence of long‐term overnutrition because studies have demonstrated a link between serum cholesterol levels and the risk for oesophageal and gastric cancer 39,40 . In line with the obtained ketone signature, the concentration of succinate, which is produced during the utilization of ketones, was increased in sera of upper GI cancer patients compared with healthy controls or PanC patients.…”
Section: Discussionsupporting
confidence: 52%
“…The increased cholesterol levels in sera of upper GI cancer patients compared with PanC patients is a further sign of prolonged starvation because it has been shown that starvation triggers cholesterol release from lysosomes 38 . However, it cannot be excluded that the elevated cholesterol levels are a consequence of long‐term overnutrition because studies have demonstrated a link between serum cholesterol levels and the risk for oesophageal and gastric cancer 39,40 . In line with the obtained ketone signature, the concentration of succinate, which is produced during the utilization of ketones, was increased in sera of upper GI cancer patients compared with healthy controls or PanC patients.…”
Section: Discussionsupporting
confidence: 52%
“…In children, the diet must meet the daily physiological activity needs and maintain body growth and development, particularly in young children. Animal foods contain potentially harmful compositions (i.e., saturated fat, cholesterol) that increase the risk of chronic disease, including: coronary heart disease, and cancer (18)(19)(20). However, animal foods are also an important source of protein for the development of LM (21).…”
Section: Introductionmentioning
confidence: 99%
“…However, there were significant inconsistencies between studies included in the meta-analysis. Furthermore, after adjusting for H. pylori , there was no association between dietary cholesterol and gastric cancer [14 ▪ ].…”
Section: Risk Factorsmentioning
confidence: 87%
“…In a meta-analysis of 14 case–control studies, high cholesterol consumption was associated with a nonlinear dose–response relationship with gastric cancer. Higher intakes of dietary cholesterol were associated with a 35% increased risk of gastric cancer (OR 1.35, CI 1.29–1.62) [14 ▪ ]. However, there were significant inconsistencies between studies included in the meta-analysis.…”
Section: Risk Factorsmentioning
confidence: 99%